A pilot study of pre-post anxiety treatment to improve academic performance for engineering students - Vitasari, Prima; Muhammad Nubli, Abdul Wahab; Herawan, Tutut; Ahmad, Othman; Suriya Kumar, Sinnadurai (Elsevier, 2011)
In this paper, we present a pilot study of pre- post treatment toward overcoming anxiety in improving academic performance for engineering's students. The anxiety level measurement was used to examine the effect of the intervention, as well to acquire the prior finding on the effectiveness of a treatment to reduce anxiety in improving academic performance. It is based on a pre post design to evaluate the effect of intervention by using breath per-minute (bpm) and grade point average (GPA). Six males and females engineering's students participated in this study. They received six sessions of treatment each for two hours of intervention. It includes breathing retreatment, relaxation, study coping skills. The results show that, the number of anxieties was significantly reduced which bpm shows t (2;5)= 4.788; p=.005 (p<.05). Furthermore, for GPA the difference is not significant with t (0;5)= -1.894; p=.117 (p>.05). Since all participants had reduced their anxiety level and improve their academic performance, we recommend that this intervention as an effective approach in reducing anxiety level.